2020
DOI: 10.1111/syen.12447
|View full text |Cite
|
Sign up to set email alerts
|

Higher‐level phylogeny of longhorn beetles (Coleoptera: Chrysomeloidea) inferred from mitochondrial genomes

Abstract: Cerambycidae (longhorn beetles) and related families in the superfamily Chrysomeloidea are important components of forest ecosystems and play a key role in nutrient cycling and pollination. Using full mitochondrial genomes and dense taxon sampling, the phylogeny of Chrysomeloidea with a focus on Cerambycidae and allied families was explored. We used 151 mitochondrial genomes (75 newly sequenced) covering all families and 29 subfamilies of Chrysomeloidea. Our results reveal that (i) Chrysomelidae (leaf beetles)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
72
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(87 citation statements)
references
References 69 publications
(143 reference statements)
15
72
0
Order By: Relevance
“…) are identical to those ofHaddad et al (2018; their fig.2), with only minor differences in nodal support; also the original cerambycid subfamilial classification ofHaddad et al (2018) is retained (additional support has been in the meantime obtained for placing Necydalinae and Parandrinae as ingroups of Lepturinae and Prioninae, respectively, e.g. inNie et al 2021). Vesperoctenus flohri, the focus of our study, is recovered within the cerambyciform family Vesperidae, sister to Vesperus (Vesperinae), with maximal nodal support.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…) are identical to those ofHaddad et al (2018; their fig.2), with only minor differences in nodal support; also the original cerambycid subfamilial classification ofHaddad et al (2018) is retained (additional support has been in the meantime obtained for placing Necydalinae and Parandrinae as ingroups of Lepturinae and Prioninae, respectively, e.g. inNie et al 2021). Vesperoctenus flohri, the focus of our study, is recovered within the cerambyciform family Vesperidae, sister to Vesperus (Vesperinae), with maximal nodal support.…”
supporting
confidence: 52%
“…Recently, phylogenomic studies have greatly improved our understanding of Coleoptera systematics and evolution (e.g., Haddad et al 2018;Shin et al 2018;McKenna et al 2019;Vasilikopoulos et al 2019). Studies of cerambyciform systematics and evolution have also been gaining momentum (e.g., Haddad and McKenna 2016;Haddad et al 2018;Lee and Lee 2020;Souza et al 2020a, b;Nie et al 2021). In this study, we sought to determine the phylogenetic placement of Vesperoctenus using phylogenomic data, since morphology alone has failed to provide a clear answer to this.…”
Section: Taxonomic Placement Referencementioning
confidence: 99%
See 1 more Smart Citation
“…Possibly, the low variability and compositional heterogeneity caused an aberrant topology recovered by individual analyses. Recent phylogenetic studies using mitochondrial genomes demonstrated that the site-heterogeneous mixture model (CAT-GTR model) implemented in PhyloBayes tends to reduce tree reconstruction artifacts [ 34 , 70 , 71 ]. Our BI analyses used site heterogeneous models and the results show their power for resolving phylogenetic relationships with Elateridae and provide for an additional example that model adequacy is critical for accurate tree reconstruction in mitochondrial phylogenomics [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chrysomeloidea cover the two largest families, Cerambycidae (longhorn beetles) and Chrysomelidae (leaf beetles), each with more than 30,000 species and about a dozen subfamilies (Nie et al 2020). Relationships among subfamilies of Chrysomelidae have been clarified over the past two decades (Reid 2000;Ge et al 2011).…”
mentioning
confidence: 99%